INTEGRASI SAPI POTONG TANAMAN SAWIT (SISKA) DAN POTENSI PENGEMBANGANNYA DI KABUPATEN PASAMAN BARAT (Studi Kasus Kelompok Tani Lubuak Gadang, Kecamatan Luak Nan Duo) - Arfa'i Arfa'i; Yuliaty Shafan Nur (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
The aim of the study was to analyze: (1) integration of beef cattle and oil palm plantations and development potential; and (2) the constraints faced in the implementation of integration programs of beef cattle and oil palm plantations. The study was conducted at farmer groups (Lubuak Gadang) in the vilage of Luhak Nan Duo County, District of East Pasaman. The study used survey method and direct observation to localized research using questionnaires. The results showed that the integration between beef cattle and oil palm plants not take place optimally, oil palm waste is not utilization for animal feed, while the use of organic vertilizer for oil palm crop has reached 100% in the form of unprocessed vertilizer. Obstacles encountered in the implementation of the integration of beef cattle and crops are oil palm farmers lack knowledge about integration and limited their knowledge of livestock waste treatment technology and feed processing of oil palm crop waste, so that the application of the integration between beef cattle and crop oil palm is not optimal.Key words: Beef cattle integration, oil palm, District of west Pasaman